2016
DOI: 10.1002/eji.201546143
|View full text |Cite
|
Sign up to set email alerts
|

CD99 isoforms regulate CD1a expression in human monocyte‐derived DCs through ATF‐2/CREB‐1 phosphorylation

Abstract: CD1a expression is considered one of the major characteristics qualifying in vitro human dendritic cells (DCs) during their generation process. Here, we report that CD1A transcription is regulated by a mechanism involving the long and short isoforms of CD99. Using a lentiviral construct encoding for a CD99 short hairpin RNA, we were able to inhibit CD99 expression in human primary DCs. In such cells, CD1a membrane expression increased and CD1A transcripts were much higher in abundance compared to cells express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Single-positive thymocytes and peripheral T cells display an exclusive expression of the full-length CD99wt isoform, whereas double-positive thymocytes and some immature T cell lines express both isoforms [ 20 ], indicating a tight correlation with T cell differentiation. In addition, the expression of the CD99 isoforms correlates with that of CD1a in human thymocytes; double-positive thymocytes express CD1a and the two forms of CD99, while single-positive thymocytes that have lost the expression of CD1a express only the long form of CD99 [ 31 ]. Among B cells, B cell precursors with acute lymphoblastic leukemia (BCPs-ALL) express mainly the long form of CD99, while in normal B cell precursors (BCPs), CD99 is downregulated during differentiation.…”
Section: Cd99 Structure and Expression In Normal Tissuesmentioning
confidence: 99%
See 2 more Smart Citations
“…Single-positive thymocytes and peripheral T cells display an exclusive expression of the full-length CD99wt isoform, whereas double-positive thymocytes and some immature T cell lines express both isoforms [ 20 ], indicating a tight correlation with T cell differentiation. In addition, the expression of the CD99 isoforms correlates with that of CD1a in human thymocytes; double-positive thymocytes express CD1a and the two forms of CD99, while single-positive thymocytes that have lost the expression of CD1a express only the long form of CD99 [ 31 ]. Among B cells, B cell precursors with acute lymphoblastic leukemia (BCPs-ALL) express mainly the long form of CD99, while in normal B cell precursors (BCPs), CD99 is downregulated during differentiation.…”
Section: Cd99 Structure and Expression In Normal Tissuesmentioning
confidence: 99%
“…CD99 has been found to participate in various steps of T and B cell development and differentiation [ 30 , 34 , 35 ] and it regulates crucial functions, such as the proliferation and activation of T lymphocytes [ 36 , 37 ], apoptosis [ 30 , 38 ], adhesion [ 19 , 34 , 39 , 40 ], lymphocytes diapedesis to the inflamed vascular endothelium [ 41 , 42 ], and intracellular membrane protein trafficking [ 43 , 44 , 45 , 46 ]. In particular, CD99 plays an active role in the transport and expression of major histocompatibility complex (MHC) class I and II and in TCR expression on thymocytes [ 43 , 44 , 45 ] and in the regulation of CD1a expression on dendritic cells [ 31 ]: thus, CD99 is a critical determinant in the orientation of the immune response.…”
Section: Cd99 Structure and Expression In Normal Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cernadas et al identified a regulatory role for CD99 in the expression of cluster of differentiation 1a (CD1a) in which isoform variants of CD99 possess opposing effects on the CD1a expression in human monocytederived DCs. While CD99 long-form decreased CD1a transcription, the short-form of CD99 counteracted this effect (Mahiddine 2016). Basically, CD1a molecules which are structurally similar to MHC I, are known for their functions in the presentation of lipid and glycolipid antigens to gamma delta T cells.…”
Section: Cluster Of Differentiation 99 (Cd99)mentioning
confidence: 99%
“…In addition, the cytoplasmic regions of the two CD99 isoforms contain shared motifs such as a zone rich in positively charged amino acids and a cysteine residue. An SHR motif for PKC and a leucine repeat are present only in the long form of CD99 (Mahiddine et al 2016 ). It has been demonstrated that the cytoplasmic domain of the long form contains two putative phosphorylation sites, a serine at amino acid residue 168 (S168) and a threonine at amino acid residue 181 (T181).…”
Section: Cd99 Gene/protein Structurementioning
confidence: 99%